The human ecological significance of urban green spaces - Tenk, Andras (Cognitive Sustainability, 2025)
The proportion of the world’s population living in cities is steadily increasing, intensifying pressure on natural resources and urban ecosystems, particularly in historically developed large cities. Urbanisation poses significant environmental challenges, including biodiversity loss, habitat fragmentation, and deteriorating urban climate conditions. This study aims to highlight the role of sustainable urbanisation and urban green infrastructure in mitigating the negative environmental and social impacts of urban growth, with a particular focus on biodiversity conservation, ecosystem services, and human well-being. The paper is based on a comprehensive review and synthesis of international and Hungarian scientific literature, policy documents, and urban planning concepts related to sustainability, green spaces, biodiversity, and urban ecology. Comparative examples from European cities are used to illustrate best practices in integrating green areas and ecological networks into urban structures. The analysis demonstrates that urban green spaces – regardless of whether they are of natural or artificial origin – provide essential ecological, climatic, social, and health-related functions. Well-connected green networks reduce habitat fragmentation, mitigate urban heat island effects, improve air quality, and contribute to physical and mental health. Furthermore, large, integrated green areas can significantly enhance urban sustainability and resilience. Preserving and expanding urban green spaces and ecological networks is a key prerequisite for livable, climate-adaptive, and healthy cities in the context of ongoing urbanisation.